Analisis Kesulitan Belajar Kimia Siswa Kelas XI pada Materi Larutan Penyangga - Sariati, Ni Kadek; I Nyoman, Suardana,; Ni Made, Wiratini, (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2020)
This research was aimed to describe (1) student’s chemistry learning disabilities and (2) the cause factors of student’s learning disabilities to understanding buffer solution topic at SMA Negeri 2 Kuta. The subjects of this research were 198 students from all class XI MIPA  and 3 chemistry teachers at SMA Negeri 2 Kuta. Method used in the research was qualitative method. The data were student’s learning achievement and information about the cause factor of student’s learning disabilities in learning buffer solution topic. The data were collected by using two-tier multiple choice test and interview. The result of this research showed that (1) student’s learning disabilities in each indicator was ranged between less difficult and most difficult and (2) the factor that cause student’s learning disabilities include internal factor and external factor. Internal factor that caused learning disabilities namely less learning interest toward chemistry, less learning motivation toward chemistry, less understanding toward buffer solution concept, less understanding toward supporting concepts of buffer solution topic, and student’s less mathematic ability. The external factor that caused learning disabilities namely negative effect of friend at same age, inadequate learning supported facilities, and teacher’s teaching method.